Green Accounting and Organization Performance: Science Mapping of Present and Future Trends - Resti Nofita; Eka Siskawati; Wiwik Andriani; Muhammad Ansar (JASF: Journal of Accounting and Strategic Finance, 2024)
Green accounting's main objective is to influence corporate behavior toward social and environmental concerns and address social issues affecting global sustainable development. Establishing green accounting practices in businesses is crucial for community concern and environmental sustainability. This research aims to explore the knowledge structure of green accounting and its impact on organizational performance. Environmental accounting is an important tool in improving the quality of environmental reporting. This study conducted a literature analysis, and the research methodology employed bibliometric analysis. VosViewer, with co-word analysis and bibliographic coupling, is specialized software used to visualize trends in research topics, authorship, and institutional affiliation. Scopus database is chosen due to its extensive coverage and indexing of important journals for articles published between 2005 and 2022. This search yielded 233 documents. This study implies that adopting green accounting has several important elements, namely integrated and transparent sustainability reports that help stakeholders make better decisions. Green accounting increases the accountability and transparency of sustainability reports, as it is supported by structured and measurable information. The board of directors’ support and good corporate governance influence the success of the sustainability report. The company's sustainability performance is assessed using complex methods and involves quantitative and qualitative indicators. This article is the first to present a scientific mapping of green accounting literature, the basis for a study on corporate sustainability performance. The results of this study give scholars, researchers, and practitioners important information about advancements in accounting science, particularly in the area of green accounting.